Second Review of the Implementation of Government Finance Statistics Framework to Strengthen Fiscal Analysis. (Policy Papers; Policy Paper ;, 2017)
This paper reports on the further developments since 2013 in the implementation of the 2010 Board decision concerning Government Finance Statistics (GFS) to Strengthen Fiscal Analysis, and develops a path to continued improvement of fiscal data in the Fund. The Board decision approved (i) developing a staggered migration strategy, including tailored capacity development inside and outside the Fund taking into consideration country-specific and fiscal surveillance needs; (ii) encouraging staff to continue the effort to routinely assess financial balance sheets during surveillance; (iii) gradually expanding the coverage of fiscal data, taking into consideration country-specific circumstances and fiscal risk assessments; and (iv) reaffirming the support for the phased implementation of the GFS over the medium term.